2020
DOI: 10.1152/ajplung.00285.2019
|View full text |Cite
|
Sign up to set email alerts
|

The dual phosphodiesterase 3/4 inhibitor RPL554 stimulates rare class III and IV CFTR mutants

Abstract: Over 2,000 mutations have been reported in the cystic fibrosis transmembrane conductance regulator ( cftr) gene, many of which cause disease but are rare and have no effective treatment. Thus, there is an unmet need for new, mutation-agnostic therapies for cystic fibrosis (CF). Phosphodiesterase (PDE) inhibitors are one such class of therapeutics that have been shown to elevate intracellular cAMP levels and stimulate CFTR-dependent anion secretion in human airway epithelia; however, the number of people with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…New research showed that phosphodiesterase (PDE) inhibitors RPL554 (Verona Pharma) can elevate intracellular cAMP in R334W Fisher rat thyroid (FRT) cells. This finding supports the therapeutic potential of RPL554 for CF patients with class III/IV variants including R334W (Turner et al, 2020). In addition, gene and molecular therapy for some mutations is also a research hot spot.…”
Section: Discussionsupporting
confidence: 74%
“…New research showed that phosphodiesterase (PDE) inhibitors RPL554 (Verona Pharma) can elevate intracellular cAMP in R334W Fisher rat thyroid (FRT) cells. This finding supports the therapeutic potential of RPL554 for CF patients with class III/IV variants including R334W (Turner et al, 2020). In addition, gene and molecular therapy for some mutations is also a research hot spot.…”
Section: Discussionsupporting
confidence: 74%
“…For measurements of short circuit current, cells were cultured at the air-liquid interface in ALI medium for 7 days before being washed 3 x with PBS and incubated for 48 h in M-BEGM. I sc measurements were then performed as previously described (Turner et al, 2020).…”
Section: Short-circuit Current (I Sc ) Measurementsmentioning
confidence: 99%
“…Recently, we demonstrated that the PDE inhibitor ensifentrine (RPL554; Verona Pharma) stimulates both wild-type CFTR and the disease causing mutant R117H-CFTR when endogenously expressed in well-differentiated primary human bronchial epithelial cells (Turner et al, 2016). We further observed that ensifentrine activates the CFTR mutants R334W-, T338I-, S549R-and G551D-CFTR when expressed in the Fisher rat thyroid (FRT) cell model (Turner et al, 2020). These data indicate that activation of cAMP/PKA signalling by ensifentrine has therapeutic potential for CFTR mutants with residual trafficking of CFTR to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…CFBE cells stably expressing mCherry-Flag-CFTR (WT, F508del, DD/AA variants or carrying G550E, R1070W, 4RK in cis with F508del) were cultured and CFTR expression was induced with doxycycline (Dox) 1 μg/mL as described (Botelho et al, 2015). Fischer rat thyroid (FRT) epithelial cells stably expressing CFTR variants (wt, G85E, R334W, T338I, R347P, F508del, V520F, S549F, G551D, M1101K, N1303K) were cultured as before (Turner et al, 2020). All cell lines were maintained in a humidified incubator at 5% CO 2 and 37°C, except during low temperature experiments, in which cells were incubated at 27°C for 24h.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in transepithelial voltage (V te ) were continuously recorded and equivalent Fsk/IBMX-stimulated short-circuit currents (I eq-sc ) were calculated by Ohm's law from V te and R te (I eq-sc =V te /R te ). For FRT cell lines, transepithelial voltage was measured at 37°C with continuous stirring by gassing with 95% O 2 and 5% CO 2 as described (Turner et al, 2020).…”
Section: Methodsmentioning
confidence: 99%